Analisis Akuntabilitas dan Transparansi Sistem Elektronik Pengadaan Barang dan Jasa Pemerintah di LKPP - Rahardjo, Sri; Bijaksana, Gena; Larasati, Kinanthi; Chamsudi, Danie Hayam Mada; Sitorus, Purbanuara Parlindungan; Kania, Dinar Dewi (Institut Transportasi dan Logistik Trisakti, 2022)
This study aims to determine the implementation of transparency and accountability in the process of procurement of goods/services electronically as well as the inhibiting factors for implementing accountability of goods/services electronically. This study uses the E-Procurement method, implementing the principle of procurement of goods/services, the government will find it easier, especially transparency and accountability that are directly related to information systems and technology. The results obtained in this study are that the procurement process for goods/services is in accordance with existing regulations and the technical team as end users already feel that the electronic procurement process is transparent. on the LPSE LKPP website. The clinical impact of this research is the government that allows for vulnerability in the form of corruption. Therefore, the government obliges every Ministry/Institution/Regional Work Unit/Institution to carry out procurement activities of government goods/services electronically, which is then referred to as e-procurement.